PEMBERIAN ZEOLIT DAN PUPUK KALIUM UNTUK MENINGKATKAN KETERSEDIAAN HARA K DAN PERTUMBUHAN KEDELAI DI ENTISOL - Surya Karto Lumban Gaol; Hamidah Hanum; Gantar Sitanggang (Jurnal Agroekoteknologi, 2014)
The Application of Zeolite and Potassium Fertilizer to Increase The Avaibility of PotassiumNutrient and Soy Growth in Entisols. Suvervised by Hamidah Hanum and Gantar Sitanggang.Theobjective of this research were: 1) determined of zeolite dosage that improved the soil chemistryproperties, 2) determinated zeolite and potassium fertilizer dosage that effected the avaibility ofpotassium and the soy growth in Entisols. The research consisted of two experiment, the first onewas the experiment of zeolite incubation, and second one was the experiment of zeolit andpotasium fertilizer. The design experiment of the first research was completely randomized designand the second one was block randomized design- factorial. The result showed that in the firstexperiment, zeolite wich incubation until 7.5 ton/hectare incerease CEC significanly, but didn’teffect the soil pH and K-exchangable. Besed the second experiment, it was know that theinteraction effect of zeolit and potasium fertilizer aplication increased potassium nutrient the plant,which the best treatment was zeolite aplication 5 ton/ hectare and potasium fertilizer 150 kg/hectare.Key words: : Entisols, Zeolite, KCl, soy growth